2021
DOI: 10.3390/jof7090730
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Combined Diagnosis and Monitoring of Aspergillus and Pseudomonas Infections: Proof of Concept

Abstract: In acutely ill patients, particularly in intensive care units or in mixed infections, time to a microbe-specific diagnosis is critical to a successful outcome of therapy. We report the application of evolving technologies involving mass spectrometry to diagnose and monitor a patient’s course. As proof of this concept, we studied five patients and used two rat models of mono-infection and coinfection. We report the noninvasive combined monitoring of Aspergillus fumigatus and Pseudomonas aeruginosa infection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…This would make it necessary to use an integrated diagnostic strategy combining BALF GM measurements with other techniques. We, therefore, investigated the diagnostic utility of multiple non-culture methods that rely on fungal infection biomarkers used in human medicine [ 29 , 35 , 36 , 37 ]. The detection of these biomarkers in equine serum and urine samples warrants further study, and the available serum data are not conclusive other than in the case of serum BDG ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would make it necessary to use an integrated diagnostic strategy combining BALF GM measurements with other techniques. We, therefore, investigated the diagnostic utility of multiple non-culture methods that rely on fungal infection biomarkers used in human medicine [ 29 , 35 , 36 , 37 ]. The detection of these biomarkers in equine serum and urine samples warrants further study, and the available serum data are not conclusive other than in the case of serum BDG ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gtx is an immunosuppressive fungal toxin that is secreted to the extracellular environment in response to fungal stress [ 40 ]. Studies have shown the utility of siderophores and/or gliotoxin in human blood and urine as useful biomarkers of Aspergillus infection, and we have detailed this recently [ 36 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dataset of mass spectra was taken from the published literature, 16 where the sample preparation and data collection processes were described in detail. Briefly, the siderophore standards (ferrioxamine E (FoxE) and a mixture of pyoverdines D and E) were purchased from EMC Microcollections GmbH (Tübingen, Germany) and spiked into the human urine and serum samples.…”
Section: Chemicals Mass Spectrometry and Personal Computer Configurationmentioning
confidence: 99%
“…An HPLC gradient can be found in the reference. 16 The liquid chromatograph was coupled to a 12 T SolariX Fourier transform ion cyclotron resonance (FTICR) mass spectrometer (Bruker Daltonics, Billerica, MA, USA) operating in positive ion mode. All LC-MS datasets were collected in triplicate, and the results were averaged.…”
Section: Chemicals Mass Spectrometry and Personal Computer Configurationmentioning
confidence: 99%
See 1 more Smart Citation